(untitled) (Eurasian Scientific Herald, 2022)
This article will focus on the use of innovative technologies in learning English at the international level. The author, relying on scientific data, analyzed the problem on the basis of the available literature and in the article considered the specifics of the use of innovative technologies in learning English at the international level.